PERILAKU BIDAN DALAM PELAKSANAAN INISIASI MENYUSU DINI (IMD) DI RSUD SUNAN KALIJAGA KABUPATEN DEMAK - Khoiriyah, Nana; Astuti, Dwi; Kusumastuti, Diah Andriani; Asiyah, Nor (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2025)
The infant mortality rate, or IMR, is the number of infant fatalities during every 1,000 live births. According to WHO, the IMR in 2023 will be 16.85 (per 1,000 live births). IMR in Indonesia is still considered high and the target of 16/1000 live births can be achieved by 2024. Most infant deaths occur in the neonatal period (0-28 days). Infant deaths that occur during the neonatal period can be prevented by providing exclusive breastfeeding starting with Early Initiation of Breastfeeding (IMD). The success of implementing IMD is influenced by the motivation of health workers such as midwives, nurses, doctors who first assist in the birthing process. Aim of the study was to analyzed the behavior of midwives in implementing Early Breastfeeding Initiation (IMD) at Sunan Kalijaga Hospital, Demak Regency. Method of the research was Qualitative method with a phenomenological approach used in this research. Data collection methods include in-depth interviews, field observations and documentation using purposive sampling techniques. Interviews were conducted with 10 participants, namely midwives in the jasmine room. Qualitative data analysis techniques were applied using Nvivo software. Test the validity of the data using theoretical triangulation and method triangulation. Result of the research was Midwives' behavior supports the implementation of IMD, but IMD still cannot be implemented optimally. Conclusion was midwives' behavior supports the implementation of IMD, but IMD still cannot be implemented optimally due to situational conditions at work, following along with friends, laziness, patient condition, busy IBS room, influence of anesthesia.